Jargon Used by Jegog Musician in Jembrana’s Local Tradition - Komang, Mitha Fridayanti; Gede Mahendrayana (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Language and culture are very relatable. In culture, there must be language used by the people to communicate with each other. Jargon is special vocabulary which had by a group of community. This study targets to analyze the jargon and the meaning of the jargon which existed on jargon used by jegog musician. The research design of this research is descriptive qualitative research. The method used to collect the data is observation and interviews. This study is use four steps of data analyzing including data collection, data reduction, data display, and conclusion drawing. The result of this research showed that jegog musician used forty-one jargons to communicate with each other. Based on the forty-one jargons found in this research, the jargons are categorized into five types. First, jargon in term of the naming of the instrument, which find ten jargons. The second, jargon in technique used on playing jegog which find thirteen jargons. Third, jargon in the naming of the notes, which find ten jargons. Then, jargon in the activity when doing jegog performance that finds six jargons. The last is jargon in term the naming of type of tabuh which find two jargons. The meaning of each jargon has their meaning to communicate in jegog musician group.